HIV Infection, as opposed to antiretroviral therapy, does not cause changes in the concentration levels of specific salivary electrolytes - Biočina-Lukenda, Dolores (Array, 2009)
Abstract: The concentration levels of salivary calcium, magnesium and zinc can vary in different localized oral, as well as systemic diseases and conditions. So far changes in the concentration levels of specific electrolytes in stimulated parotid saliva in HIV-positive/AIDS patients have been proven. The objective of this research was not only to study the concentration levels of calcium in non-stimulated total saliva, but also the concentration levels of magnesium and zinc, which have not been studied so far, and the influence of antiretroviral therapy (HAART). This research was conducted on 60 healthy subjects with an average age of 40.4 years, and 60 HIV-positive patients with an average age of 43.7 years, 45 of whom took HAART therapy. The concentration levels of calcium, magnesium and zinc in saliva were determined by means of an atomic absorption spectrophotometry.